PLAYFUL ACTIVITIES AS A MOTIVATIONAL FACTOR IN JUDO CLASSES TO CHILDREN (Fiep Bulletin - online, 2014)
During the apprenticeship phase of judo a great deal of attention is required for the execution of its techniques, what turns out to be upsetting at times due to the exhaustive repetition of movements. Because judo is a fighting match, both the "Ukemis", which are cushioning techniques, as well as the striking of blows are tiring and often lead to a certain lack of motivation within students. This being the case, a solution to make classes more attractive is the use of playful activities. Therefore, the purpose of this study is to verify the possibility of the use of playful class activities by judo instructors and in which fundamentals they could depend for such use. In order to achieve the results, a 20-question questionnaire comprising both open and multiple-choice questions was prepared and sent to 45 judo instructors in several locations in the city of Rio de Janeiro. Graphics have been produced aiming at the analysis of the data generated by both the multiple-choice and the direct and objective questions. Concerning the open questions, the answers were compared through charts, identifying four ideas related to the use of playful activities as a motivational means: apprenticeship, discipline, socialization and warming up, generating, this way, the creation of four categories of analysis (Moura, Ferreira and Paine, 1998). The conclusion showed that most instructors make use of playful activities in their classes, making it easier for the learning of judo, concentrating them on the warming up. The utilization focus is linked to the idea of motivating the classes, making it easier to learn, fortifying the socialization of the children and, to a certain extent, increasing the pleasure of being in class following the discipline imposed by the practice. Nevertheless, when justifying the use of playful activities, the instructors base themselves more strongly on their experience acquired in the area of sports, either as  athletes or former athletes, than on their academic background as demanded by the Physical Education State Body 'Conselho Regional de Educação Física'.
Keywords: playful activities; judo; training